PROPHYLAXIS AND THERAPY OF IMPAIRED GLUCOSE TOLERANCE IN LONG-TERM THERAPY OF THE PATIENTS WITH SEVERE DERMATOSES WITH GLUCOCORTICOSTEROID HORMONES - Kutasevych, Y. F.; Levchenko, О. O.; Popov, M. M. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
Impaired glucose tolerance (IGT) is the most wide-spread complication of long-term therapy of severe dermatoses with glucocorticoid hormones among possible steroid-induced disturbances of carbohydrate metabolism being also a component part of the conception « state prior to the development of diabetes». The mentioned complication leads to the development of cardiovascular pathology which in its turn worsens both the general state of the patient and aggravates the dermatosis course. In this connection the work on prophylaxis and therapy of steroid-induced IGT with metformin preparation having a number of therapeutic effects on human organism besides main hypoglycemic activity in patients with skin diseases was carried out.